2014
DOI: 10.1016/j.neuro.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of binge methamphetamine injections on the mRNA expression of histone deacetylases (HDACs) in the rat striatum

Abstract: Methamphetamine use disorder is characterized by recurrent binge episodes. Humans addicted to methamphetamine experience various degrees of cognitive deficits and show evidence of neurodegenerative processes in the brain. Binge injections of METH to rodents also cause significant toxic changes in the brain. In addition, this pattern of METH injections can alter gene expression in the dorsal striatum. Gene expression is regulated, in part, by histone deacetylation. We thus tested the possibility that METH toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
0
20
1
Order By: Relevance
“…HDACs modulation by psychostimulants was previously reported. Exposure of adult rats to METH led to altered expression patterns of several HDACs, including HDAC1 and HDAC2 Martin et al, 2012), and HDAC6, HDAC8-HDAC11, SIRT2, SIRT5 and SIRT6 (Omonijo et al, 2014). These expression patterns seem to depend on the METH dose and period of exposure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…HDACs modulation by psychostimulants was previously reported. Exposure of adult rats to METH led to altered expression patterns of several HDACs, including HDAC1 and HDAC2 Martin et al, 2012), and HDAC6, HDAC8-HDAC11, SIRT2, SIRT5 and SIRT6 (Omonijo et al, 2014). These expression patterns seem to depend on the METH dose and period of exposure.…”
Section: Discussionmentioning
confidence: 96%
“…There is growing evidence that HDACs inhibition is strongly associated with decreased cell mobility, which is of particular interest in the oncology field (Hrabeta et al, 2014;Ocker and Schneider-Stock, 2007). Although there are several studies showing that METH and other psychostimulants affect the expression of HDACs (Cassel et al, 2006;Host et al, 2011;Martin et al, 2012;Omonijo et al, 2014), and in particular the expression of HDAC6 (Omonijo et al, 2014), the effect of METH in microtubules acetylation was not yet explored. Therefore, we hypothesized that METH-induced regulation of HDACs activity, and in particular of HDAC6, may also mediate the structural loss observed in METH-exposed endothelial cells.…”
Section: Introduction Methamphetamine (Meth) Is a Powerful Psychostimmentioning
confidence: 99%
“…In summary, our previous and current results, together with the finding that morphine-increased LINE-1 expression did not correlate with LINE-1 hypomethylation [41], point to mechanisms independent of cytosine methylation at the LINE-1 promoter CpG sites. Potential mechanisms regulating LINE-1 activation and transcription during METH administration include LINE-1 hydroxymethylation [106], as well as HDACs-mediated histone modifications, small interfering RNAs, small piRNAs, P1-LINE-1 RNA, DNA-editing proteins, and WTN pathway [50,105,[107][108][109][110][111]. As compared to saline controls, rats that self-administered high doses of METH showed differential DNA hydroxymethylation within LINE; therefore, this mechanism is the one most likely responsible for METH-triggered LINE-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT4 is highly expressed in rat astrocytes (Komlos et al, 2013). It is reported that SIRT5 is expressed in rat striatum (Omonijo et al, 2014). Not much is known about the astrocyte-specific expression of SIRT6 and SIRT7, that are nuclear enzymes except for that fact that they are expressed in rat hippocampus and cerebral cortex (Braidy et al, 2015).…”
Section: Sirtuins Expression In Astrocytesmentioning
confidence: 99%